2020
DOI: 10.21203/rs.3.rs-51212/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical outcomes of acute pulmonary embolectomy as the first-line treatment for massive and submassive pulmonary embolism:a single-centre study in China

Abstract: Background: Acute pulmonary embolism (PE) is one of the most critical cardiovascular diseases. PE treatment ranges from anticoagulation, and systemic thrombolysis to surgical embolectomy and catheter embolectomy. Surgical pulmonary embolectmy (SPE) indications and outcomes are still controversial. Although there have been more favourable SPE reports over the past decades, SPE has not yet been considered broadly as an initial PE therapy and is still considered as a reserve or rescue treatment for acute massive … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Small modern series of surgical embolectomy for the management of acute PE reported a dramatic improvement in postoperative in-hospital mortality, ranging from 2.3 to 13.2%, with mortality associated largely with preoperative CPR. [87][88][89][90] We performed a systematic review and metaanalysis of 17 studies including a total of 327 PE patients managed with ECMO life support. 60 This study found that mechanical pulmonary reperfusion (including surgical [86%] and catheter-based embolectomy) seemed to be more effective than other strategies (i.e., systemic thrombolysis, catheter-directed thrombolysis, and stand-alone approach), for mitigating the mortality rate (OR, 0.44; 95% CI, 0.24-0.82), and demonstrated a similar risk of bleeding (OR, 1.27; 95% CI, 0.54-2.96).…”
Section: Ecmo and Surgical Embolectomymentioning
confidence: 99%
“…Small modern series of surgical embolectomy for the management of acute PE reported a dramatic improvement in postoperative in-hospital mortality, ranging from 2.3 to 13.2%, with mortality associated largely with preoperative CPR. [87][88][89][90] We performed a systematic review and metaanalysis of 17 studies including a total of 327 PE patients managed with ECMO life support. 60 This study found that mechanical pulmonary reperfusion (including surgical [86%] and catheter-based embolectomy) seemed to be more effective than other strategies (i.e., systemic thrombolysis, catheter-directed thrombolysis, and stand-alone approach), for mitigating the mortality rate (OR, 0.44; 95% CI, 0.24-0.82), and demonstrated a similar risk of bleeding (OR, 1.27; 95% CI, 0.54-2.96).…”
Section: Ecmo and Surgical Embolectomymentioning
confidence: 99%
“…29 30 31 A single-center study in China reported excellent results with an overall mortality 7.31%, with all three mortalities occurring in the massive PE group. 32 CPB has become synonymous with open heart procedures, and results continue to show that preoperative hemodynamic support may improve results of surgical pulmonary embolectomy, especially high-risk patients experiencing cardiac arrest. 33 34 John Gibbon would be proud to see how far we have come in the treatment of PEs; results continue to show that surgery could be offered as a safe and effective primary approach in both submassive and massive PE patients.…”
Section: Validationmentioning
confidence: 99%